Pengaruh Perbandingan Daun Putri Malu (Mimosa pudica Linn.) dan Bunga Melati (Jasminum sambac (L.) Ait.) Terhadap Karakteristik Teh Celup Wangi - Olivia Isabella, Michelle; Kencana Putra, I Nengah; Kadek Diah Puspawati, Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p01, 2021)
This study aimed to determine the effect of the comparison of Mimosa pudica L. leaves and jasmine on the characteristics of scented tea bag and find out the comparison of Mimosa pudica L. and jasmine to obtain the best characteristics of the scented tea bag. The experimental design used was Completely Randomized Design with the comparison treatment Mimosa pudica L. leaves and jasmine as a treatment which consist of 5 levels: 100%:0%, 85%:15%, 70%:30%, 55%:45%, and 40%:60%. The treatment was repeated three times, resulting in 15 experimental units. The data obtained then analyzed by the Analysis of Variance, and if the treatments had a significant effect, continued with the Duncan Multiple Range Test. The result showed that the comparison of Mimosa pudica Linn. and jasmine had significant effect on water content, water-soluble extractive, total phenol, total flavonoid, IC50 value, taste (scoring and hedonic test), aroma (scoring and hedonic test), and overall acceptance. The comparison of 70% Mimosa pudica L. and 30% jasmine had the best characteristic, which had a water content 10.97%, water-soluble extractive 22.59%, total phenol 3.70 mg GAE/g, total flavonoids 1.05 mg QE/g, IC50 value 128.73 ppm. The brewed tea bag had a slightly liked color, a slightly liked and slightly jasmine aroma, a slightly bitter and slightly liked taste, and a slightly liked overall acceptance.